2022
DOI: 10.1111/bdi.13139
|View full text |Cite
|
Sign up to set email alerts
|

Impaired robust interhemispheric function integration of depressive brain from REST‐meta‐MDD database in China

Abstract: Background Recently, functional homotopy (FH) architecture, defined as robust functional connectivity (FC) between homotopic regions, has been frequently reported to be altered in MDD patients (MDDs) but with divergent locations. Methods In this study, we obtained resting‐state functional magnetic resonance imaging (R‐fMRI) data from 1004 MDDs (mean age, 33.88 years; age range, 18–60 years) and 898 matched healthy controls (HCs) from an aggregated dataset from 20 centers in China. We focused on interhemispheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…CBF in the parietal lobe, including S1 and PCC, was negatively associated with the severity of depression and childhood maltreatment in MDD. 40,42 S1 is involved in pain and emotional experiences processing. 43 MDD with CM performed lower amplitude of low-frequency fluctuations in LS1, contributing to abnormal sensation.…”
Section: Discussionmentioning
confidence: 99%
“…CBF in the parietal lobe, including S1 and PCC, was negatively associated with the severity of depression and childhood maltreatment in MDD. 40,42 S1 is involved in pain and emotional experiences processing. 43 MDD with CM performed lower amplitude of low-frequency fluctuations in LS1, contributing to abnormal sensation.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we employed data from International Big‐Data Center for Depression Research (IBCDR), which was collected in China (The data is available by request from any qualified investigator. Website: http://yanlab.psych.ac.cn/IBCDR ) (Deng et al, 2022 ; Ding et al, 2022 ). The data use agreement was attached as supplementary material.…”
Section: Methodsmentioning
confidence: 99%
“…To address the issue of sample-size, we initiated the Depression Imaging REsearch ConsorTium (DIRECT) (45) and and carried out an initial meta/mega-analysis (NMDD = 1300), referred to as REST-meta-MDD (40). Studies from the initially shared DIRECT data revealed multiple MDDrelated abnormalities including in network FC, whole-brain FC topological and dynamic features, and functional lateralization (40,(46)(47)(48)(49)(50)(51)(52). The DIRECT Phase I neuroimaging data were preprocessed using a volume-based approach (DPARSF (53,54)), producing voxel-wise BOLD time series at each participating hospital which were then shared.…”
Section: Introductionmentioning
confidence: 99%